Readability of Online Patient Education Materials for Dental Radiology - Yeung, Andy Wai Kan (Current Dentistry, 2021)
BackgroundDental patients may seek and read online patient education materials pertaining to dental radiology.ObjectiveThe objective of this study was to quantitatively evaluate the readability of online patient education materials pertaining to dental radiology.MethodsAll patient education articles available in 2021 from professional societies and authoritative bodies related to dental radiology were reviewed. Each article was assessed using the Gunning Fog index, Coleman Liau index, Flesch-Kincaid Grade level, Automated Readability index (ARI), Simple Measure of Gobbledygook (SMOG) and Flesch Reading Ease score. Contextual information was recorded in terms of the perspective from which the webpage was written (first, second, or third-person perspective), modalities mentioned (bitewing, periapical, occlusal, panoramic, cephalometric, or cone beam [CB] CT/CT), any radioprotection measures explained (for general, pregnancy, or children), and indications of imaging mentioned.ResultsNine relevant webpages were identified. None of the major dental radiology associations (except the United States one) provided such online information. All but one required about a tenth-grade reading level to understand the content easily.ConclusionNone of the webpages fulfilled the recommendations from the National Institute of Health and the American Medical Association of being written below a seventh-grade level. More online patient education materials for dental radiology were recommended, and they should be written in a more easily understood way.
Keywords: website